2023
DOI: 10.3390/w15101830
|View full text |Cite
|
Sign up to set email alerts
|

Drag Coefficient Parameterization under Hurricane Wind Conditions

Abstract: The influence of small-scale processes at the ocean–atmosphere boundary layer such as spray and foam on the surface waves prediction is studied. Estimates of the effect of including the exact number of specific fragmentation “parachute” type in the spray on the resulting drag coefficient is shown. For the estimates, the numerical simulations within WAVEWATCH III wave model are performed. The parameterizations of wind input are tested within WAVEWATCH III wave model: default ST4 and ST6 parameterizations and th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…This discrepancy occurs because the linear relationship of the surface drag coefficient with the wind speed proposed by Wu (1980) overestimates the drag coefficient at high wind speeds (Moon et al, 2003). Recent studies have indicated a decay in the surface drag coefficient at high wind speeds (Chen et al, 2022;Kuznetsova et al, 2023). To elucidate the attenuation mechanism of the sea surface drag coefficient influenced by droplets at high wind speeds, an analysis was conducted based on Equation ( 5), considering the influence of droplets on the surface drag coefficient.…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy occurs because the linear relationship of the surface drag coefficient with the wind speed proposed by Wu (1980) overestimates the drag coefficient at high wind speeds (Moon et al, 2003). Recent studies have indicated a decay in the surface drag coefficient at high wind speeds (Chen et al, 2022;Kuznetsova et al, 2023). To elucidate the attenuation mechanism of the sea surface drag coefficient influenced by droplets at high wind speeds, an analysis was conducted based on Equation ( 5), considering the influence of droplets on the surface drag coefficient.…”
Section: Discussionmentioning
confidence: 99%